2013
DOI: 10.1371/journal.pcbi.1003004
|View full text |Cite
|
Sign up to set email alerts
|

Systems Model of T Cell Receptor Proximal Signaling Reveals Emergent Ultrasensitivity

Abstract: Receptor phosphorylation is thought to be tightly regulated because phosphorylated receptors initiate signaling cascades leading to cellular activation. The T cell antigen receptor (TCR) on the surface of T cells is phosphorylated by the kinase Lck and dephosphorylated by the phosphatase CD45 on multiple immunoreceptor tyrosine-based activation motifs (ITAMs). Intriguingly, Lck sequentially phosphorylates ITAMs and ZAP-70, a cytosolic kinase, binds to phosphorylated ITAMs with differential affinities. The purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 47 publications
2
54
2
Order By: Relevance
“…By comparison, only type β Ca 2+ was observed in 34 T cells that were also engaged with OVA pMHC by 10-pN force-clamp but accumulated <10 s bond lifetime (Figure 6B, highlighted center panel, ). Thus, single-cell analysis reveals that Ca 2+ response is digital( Altan-Bonnet and Germain, 2005; Mukhopadhyay et al, 2013) with a threshold of 10-s total lifetime, an optimal 60-s window, and zero time-delay of accumulation for Ca 2+ triggering. The optimal initial 60-s window suggests a kinetic mechanism for efficient antigen scanning: T cells in vivo would lose interest in an APC after short initial contact times (presumably from endogenous pMHCs on the APC) whereas effective serial engagement with cognate antigen that generated longer cumulative bond lifetimes would deliver a timely stop signal for the T cell to appropriately act upon.…”
Section: Resultsmentioning
confidence: 99%
“…By comparison, only type β Ca 2+ was observed in 34 T cells that were also engaged with OVA pMHC by 10-pN force-clamp but accumulated <10 s bond lifetime (Figure 6B, highlighted center panel, ). Thus, single-cell analysis reveals that Ca 2+ response is digital( Altan-Bonnet and Germain, 2005; Mukhopadhyay et al, 2013) with a threshold of 10-s total lifetime, an optimal 60-s window, and zero time-delay of accumulation for Ca 2+ triggering. The optimal initial 60-s window suggests a kinetic mechanism for efficient antigen scanning: T cells in vivo would lose interest in an APC after short initial contact times (presumably from endogenous pMHCs on the APC) whereas effective serial engagement with cognate antigen that generated longer cumulative bond lifetimes would deliver a timely stop signal for the T cell to appropriately act upon.…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to note that our observations are pertinent given the availability of chimeric antigen receptors (CARs) that make use of the CD3ζ chain to transduce intracellular signals and activate the antigenic cell of interest (47, 48). It may be possible that certain ITAMs with optimal affinities for Zap70 can be used to optimize TCR reactivity to target antigen with a decrease off target effects (25). By substituting all of the ITAM sequences for a single, identical ITAM sequence, our studies have helped clarify the non-redundant role of the 10 ITAM sequences found within the TCR:CD3 complex.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence suggests that the ITAMs contained in the individual CD3 subunits may allow for differential recruitment of adaptor molecules including ζ-associated protein of 70 kDa (ZAP-70), Grb2 and phospholipase C (PLC)-γ (24). Interestingly, the number and ITAM sequence is also important in the design of chimeric antigen receptors (CAR) that utilize the TCR ζ chain, where studies indicate that ITAM affinity for ZAP-70 can be utilized to optimize potency of CAR reactivity (25). However, it still remains to be determined whether the specific ITAM sequences found within the CD3γε, CD3δε and ζζ subunits are necessary or redundant for optimal TCR signaling, T cell development and function.…”
Section: Introductionmentioning
confidence: 99%
“…deterministic Boolean analysis), we used the asynchronous update rule that eliminates such errors that might creep in due to the use of synchronous or deterministic Boolean approach. This approach gives us the liberty to get a more dynamic way of analysing the large Tcell network as compared to other logical models published earlier (Saez-Rodriguez et al 2007;Wittmann et al 2009;Saadatpour et al 2011;Mukhopadhyay et al 2013). In this study, the asynchronous update of the Boolean transition equations reveals the fluctuations and oscillation patterns of protein expression in many diseased/mutated conditions performed in silico (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…Several modelling and computational studies (Sherriff and Sarkar 2008) on the core T-cell signalling network have revealed numerous hidden facts about this pathway, but so far no study has considered the importance of all the coreceptor signalling pathways including the core network during T-cell activation. A previous study using systems level model on the sequential phosphorylation of T-cell antigen receptor (TCR) by LCK molecule has revealed the importance of having multiple phosphorylation sites on TCR and the successive differential binding of ZAP70 on those phosphorylated sites with ultrasensitivity or switch-like response architecture in TCR signalling network (Mukhopadhyay et al 2013). In another study, the activation mechanism of primary T-cell by TCR, CD4/CD8 co-receptor, and CD28 molecules after encountering with APC has been studied using Boolean formalisms (Saez-Rodriguez et al 2007).…”
Section: Discussionmentioning
confidence: 99%